2013
DOI: 10.1155/2013/582526
|View full text |Cite|
|
Sign up to set email alerts
|

Neurogenesis and Increase in Differentiated Neural Cell Survival via Phosphorylation of Akt1 after Fluoxetine Treatment of Stem Cells

Abstract: Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRI). Its action is possibly through an increase in neural cell survival. The mechanism of improved survival rate of neurons by FLX may relate to the overexpression of some kinases such as Akt protein. Akt1 (a serine/threonine kinase) plays a key role in the modulation of cell proliferation and survival. Our study evaluated the effects of FLX on mesenchymal stem cell (MSC) fate and Akt1 phosphorylation levels in MSCs. Evaluation tests included reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…We found that after STOX1 knockdown in cultured epithelial cells, expression of markers for proliferation (PCNA and cyclin A, cyclin E) (26,42) was significantly reduced, but up-regulated following STOX1 over-expression. During mammalian organogenesis, the AKT pathway regulates both cell proliferation and programmed cell death (11,43). Our results further show that shSTOX1 inhibited phosphorylation of AKT in the inner ear utricular epithelial cells, while over-expression of STOX1 activated phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 71%
“…We found that after STOX1 knockdown in cultured epithelial cells, expression of markers for proliferation (PCNA and cyclin A, cyclin E) (26,42) was significantly reduced, but up-regulated following STOX1 over-expression. During mammalian organogenesis, the AKT pathway regulates both cell proliferation and programmed cell death (11,43). Our results further show that shSTOX1 inhibited phosphorylation of AKT in the inner ear utricular epithelial cells, while over-expression of STOX1 activated phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 71%
“…After 10 days (d) in culture, expanded cell populations were transferred into a medium consisting of DMEM (Gibco‐BRL) containing 10% FBS and 25 µg/mL gentamicin (Sigma, USA). The cells were pre‐treated with di‐methyl sulfoxide (DMSO, Sigma) and exposed to 10 −6 M all‐ trans RA (Sigma, USA) for 7 d as described previously (Rahmani et al, ). RA diluted in absolute ethanol was added to the culture medium twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…On days 0, 7, and 14, total ribonucleic acid was extracted from cells using Trizol (Gibco, UK) (Rahmani et al, ). Reverse transcription was carried out with AMV reverse transcriptase (Takara, Japan) for 1 h at 42°C, followed by inactivation for 10 min at 95°C and cooling to 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial derived stromal cells from human endometrium were isolated and demonstrated the potential of differentiation into different lineage cells (Noureddini et al, ; Shoae‐Hassani et al, ,; Rahmani et al, ; Verdi et al, ). It has been shown that human endometrial cells express some levels of pluripotent factors (Kyo et al, ; Gotte et al, ), which, with additionally defined factors, result in significantly more efficient and accelerated generation of iPSCs compared with somatic cells (Park et al, ).…”
Section: Introductionmentioning
confidence: 99%